Evaluasi Pelaksanaan Peraturan Daerah Nomor 6 Tahun 2014 Tentang Rencana Induk Pembangunan Kepariwisataan Kabupaten Pandeglang Tahun 2015-2025 (Studi Kasus Pada Objek Wisata Air Panas Cisolong, Kecamatan Kaduhejo, Kabupaten Pandeglang) - Lia Apriliani; Rahmawati; Leo Agustino (Epistemik: Indonesian Journal of Social and Political Science, 2022)
The focus of this study is the Evaluation of the Implementation of Regional Regulation Number 6 of 2014 concerning the Master Plan for Regional Tourism Development in 2015-2025 (Case Study on Cisolong Hot Spring Tourism Object, Kaduhejo District, Pandeglang Regency). Identifying the problem is the lack of infrastructure for tourism public facilities, the weak empowerment of the tourism community in Cisolong tourist attractions as tourist actors and the lack of optimal tourism promotion carried out by the Pandeglang Regency Government. The formulation of the problem is how to evaluate the implementation of regional regulations. The theory used in this study uses the theory of policy evaluation criteria according to Leo Agustino (2020: 195). This research uses descriptive research methods with a qualitative approach. The results showed that the Evaluation of the Implementation of Regional Regulation Number 6 of 2014 on the Cisolong hot spring tourist attraction has not been carried out optimally because in the implementation of regional regulations there are still shortcomings in governance in tourist destinations, then traction, accessibility to bags, amenity and promotion that have not been maximized and budget constraints, weak the role of tourism human resources in the tourism industry in Pandeglang Regency. Recommendations that can be given are to carry out more optimal destination management by cooperating with the community and the private sector, conducting continuous training and coaching, strengthening tourism promotion and improving tourism attractions, accessibility and amenity.